Aetiological factors in persistent sputum production: a case-control study. Issue 1 (February 1993) - Cullinan, P
Abstract : STUDY OBJECTIVE–The aim was to explore the aetiological roles of smoking, occupational exposure, childhood respiratory illness, and atopy in persistent sputum production. DESIGN–This was a case-control study. Data were obtained using a questionnaire administered by two observers blind to the subjects' status. Information was sought on lifetime smoking, occupation, hospital admissions due to respiratory disease, and respiratory disease history. SETTING–Four general practices in south east England in 1990, with a total population of about 30, 000. SUBJECTS–Cases were subjects aged 5 to 54 years with sputum production; one control was selected per case, matched by general practice, age, and sex, forming 210 matched pairs (88% response rate). MAIN RESULTS–Cigarette smoking remains an important cause of persistent sputum production: the odds ratio (95% confidence interval) for current smoking was 7.9 (3.6-20.4). A dose-response relationship was confirmed, with falling risk estimates after stopping smoking. The association of sputum production with occupational exposure to respiratory irritants, which was independent of smoking, was confined to men (odds ratio 2.4, 1.0-6.0) and largely attributable to very heavy exposure. Examination of the relationship with early respiratory disease suggested that much, though not all, was attributable to wheezing illnesses first manifest in childhood. CONCLUSIONS–Aetiological fractions derived from the results suggest that in the general population of south east England approximately 68% of all cases of persistent sputum production can be independently attributed to current cigarette smoking, 17% to heavy occupational exposure to respiratory irritants, and 13% to wheezing illnesses first manifest in early childhood.